Waste less time on Facebook — follow Brilliant.
×

Psyched up!

In the theory of learning in psychology, probabilities t and p and a constant b are related by: t = (1-b)p

Show that this equation may be written as: 1-t = (1-b)(1-p) + b

How?

Note by Xavier Fernandez
1 year, 5 months ago

No vote yet
1 vote

Comments

Sort by:

Top Newest

\(1 -t = 1-(1-b)p\)

\(=1-(1-b)\left(1-(1-p)\right)\)

\(=1-(1-b)+(1-b)(1-p)=b+(1-b)(1-p)\)

Hence, proved. Janardhanan Sivaramakrishnan · 1 year, 5 months ago

Log in to reply

×

Problem Loading...

Note Loading...

Set Loading...